Measurement of Noise Intensity in the Al-Mahirah Lamdingin Market Area, Banda Aceh City in 2024 - Ali Muktadin, Rahmat; Fahmi Ichwansyah; Tiara Mairani (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Noise is a fairly important issue, especially in relation to comfort. Excessive noise levels in markets can have very dangerous negative impacts in many ways, namely health impacts as well as psychological and technical impacts. Objective: The purpose of this study is to identify the noise level that occurs in the market area using a Sound Level Meter (SLM) and to map the noise level in the Al-mahirah Lamdingin market. Methods: This study uses an observation method, data collection is carried out by direct observation and measurement of the research object. The sample in this study is one of the sectors of the community trade center, namely the Al-Mahirah Lamdingin market in Banda Aceh city which consists of 93 kiosks with 639 traders. Inclusion criteria are places where people often gather and pass by, areas that are flanked by lots of noise and come from different sources and machines that operate more than 4 hours in 1 day. Exclusion criteria are locations/areas that do not have noise sources and are far from the main road shoulder, machines that operate for less than 4 hours and operate only at certain times. Data were analyzed using Microsoft Excel software. Results: The results of the study showed that the noise intensity at the Al-Mahirah Lamdingin Market was already in the risky category because it had the highest noise intensity of 55.2 dBA, but did not exceed the threshold value that had been set, namely 65 dBA. Conclusion: Based on the measurement of noise intensity in the Al-Mahirah Lamdingin market, the noise intensity value does not exceed the noise quality standard value but is already at a risky stage because the measurement results are close to the set quality standard and the frequency and time of noise exposure are quite long with the target group. It is necessary to carry out control at each point such as changing the layout of the machine so that the noise does not collect in one place and the use of Hearing Protection Equipment (APT) or it can be by controlling the device, be it equipment renewal or repair.